Modern methods to determine vitamin E in foods and feeds - Bara, Camelia; Bara, Lucian; Bara, Vasile; Bara, Ligia; Domuta, Cristian (Acta Agraria Debreceniensis, 2010)
Highly specific and sensitive, the proposed fluorometric method for determining α-tocopherol is robust and fairly fast. Ithas been tested in parallel with a conventional thin layer chromatographic method on foods and feeds. The only necessarycleanup is the usual saponification. The unsaponificable fraction can be extracted with ethyl ether or, preferably, withExtrelut columns. Reagents and their solvents are added to the isooctane solution before each successive reaction and arethen eliminated by partition with water. The α-tocopherol (α-T) derivative always remains in isooctane. The first step isnitrosation and elimination of tocopherols and tocotrienols other than α-isomers. α-T is then oxidized to α-tocored (α-TR)with a mixture of sulfuric acid, ferric chloride, and iodine bromide. Α-TR is then condensed to a new reagent: 4,5-dimethylo-phenylenediamine. The phenazine formed is strongly fluorescent. Iodine and bromine add to the double bonds of α-tocotrienol present and quench the fluorescence of its phenazine.